Science journal editors' views on publication ethics: results of an international survey. Issue 6 (29th May 2009) - Wager, E; Fiack, S; Graf, C; Robinson, A; Rowlands, I
Abstract : Background: Breaches of publication ethics such as plagiarism, data fabrication and redundant publication are recognised as forms of research misconduct that can undermine the scientific literature. We surveyed journal editors to determine their views about a range of publication ethics issues. Methods: Questionnaire sent to 524 editors-in-chief of Wiley-Blackwell science journals asking about the severity and frequency of 16 ethical issues at their journals, their confidence in handling such issues, and their awareness and use of guidelines. Results: Responses were obtained from 231 editors (44%), of whom 48% edited healthcare journals. The general level of concern about the 16 issues was low, with mean severity scores of <1 (on a scale of 0–3) for all but one. The issue of greatest concern (mean score 1.19) was redundant publication. Most editors felt confident in handling the issues, with <15% feeling "not at all confident" for all but one of the issues (gift authorship, 22% not confident). Most editors believed such problems occurred less than once a year and >20% of the editors stated that 12 of the 16 items never occurred at their journal. However, 13%–47% did not know the frequency of the problems. Awareness and use of guidelines was generally low. Most editors were unaware of all except other journals' instructions. Conclusions: Most editors of science journals seem not very concerned about publication ethics and believe that misconduct occurs only rarely in their journals. Many editors are unfamiliar with available guidelines but would welcome more guidance or training.